1990
DOI: 10.1111/j.1399-3054.1990.tb08707.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and firmness determination of ripening tomato fruit

Abstract: Tomato (Lycopersicon esculentum Mill.) genotypes varying in intrinsic firmness were examined to determine the quantitative relationships between polygalacturonase (EC 3.2.1.15) activity, firmness and other ripening parameters including rate (days from mature‐green to full red) and intensity (rate of ethylene production at climacteric peak) of ripening. Texture, respiration and ethylene production were monitored in the immature‐green through the red (ripe) stages of development. Polygalacturonase activity was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…BR tomatoes were more sensitive to impacts than MG, as previously reported (Halsey, 1955;Hatton and Reeder, 1963;Sargent et al, 1989a). Compression testing has shown that BR tomatoes are measurably softer than MG fruit when deformation is applied along the equatorial plane (Ahrens et al, 1987;Ahrens and Huber, 1990;Kader et al, 1978). In this study, single drops of BR tomatoes from 10 cm caused IB in 15% to 73% of fruit, while two drops on a single location from this height caused 50% to 67% (Tables 1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BR tomatoes were more sensitive to impacts than MG, as previously reported (Halsey, 1955;Hatton and Reeder, 1963;Sargent et al, 1989a). Compression testing has shown that BR tomatoes are measurably softer than MG fruit when deformation is applied along the equatorial plane (Ahrens et al, 1987;Ahrens and Huber, 1990;Kader et al, 1978). In this study, single drops of BR tomatoes from 10 cm caused IB in 15% to 73% of fruit, while two drops on a single location from this height caused 50% to 67% (Tables 1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Fruit firmness, as measured by resistance to deformation, also varies with cultivar and most likely influences cultivar susceptibility to IB. 'Sunny' was determined to be moderately firm among five cultivars of fresh-market tomatoes, when measured at the IB-sensitive BR stage (Ahrens and Huber, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…There is a rough correlation between the level of polygalacturonase activity and the degree of softening among different cultivars and mutants of tomato (Brady et ai., 1983;Speirs et al, 1989;Ahrens and Huber, 1990). However, experiments designed to directly address the role of polygalacturonase during ripening indicate that polygalacturonase activity alone is not sufficient for fruit softening (Giovannoni et al, 1989;Schuch et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The force required to penetrate the fruit is recorded as a firmness index (Kojima et al 1991(Kojima et al , 1992. Flat probe is also used for compression of excised fruit (Arhens, and Huber 1990). Since the rate of travel is precisely controlled, the force data are more reliable and reproducible than those by a Magness-Taylor puncture tester.…”
Section: Destructive Methodsmentioning
confidence: 99%